Integrated and Open Interpreter Education - Maroney, Elisa; Smith, Amanda; Hewlett, Sarah (Open textbook library., 2019)
This Open Educational Resource (OER) on interpreting offers authors and readers free and open access to current, relevant, easy-to-access, and free materials. The editors have created a space where emerging scholars in the field of signed language interpreting make contributions with the ability to revise as the interpreting studies discipline and the scholars, themselves, develop and change. This OER provides faculty and students readings and practical application experiences that connect program specific coursework and concepts across the interpreter education curriculum emphasizing the holistic nature of the field of interpreting.